Use of 1-Methylcyclopropene (1-MCP) on Tomato and Avocado Fruits: Potential for Enhanced Shelf Life and Quality Retention - Don Huber; Jiwon Jeong; Mark Ritenour (EDIS)
This document is HS-914, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January, 2003.